Illzach Bridge: Innovative Repair of Orthotropic Deck Using Ultra-High-Performance Fibre-Reinforced Concrete—Return After 5 Years. Issue 3 (2nd July 2020) - Champenoy, Damien; Généreux, Grégory; Hajar, Ziad; Simon, Alain; Fyon, Sébastien
Abstract: Built in 1970, the Illzach bridge is located near Mulhouse in eastern France. It is a single 106 m span bridge carrying two traffic lanes, with two lateral steel trusses and an orthotropic slab with transverse cross-beams. After the detection of numerous cracks in the deck welds in 2009, a repair solution, based on the replacement of the asphalt layer by a thin slab of ultra-high-performance fibre-reinforced concrete (UHPFRC), with local connection to the orthotropic steel deck, was adopted. The strengthening technique, called Orthodalle ®, was designed as a result of the Orthoplus national research project (2007–2011) and the works were performed during summer 2011. After introducing the bridge and its problems, this paper presents the design, implementation, monitoring and tests of this innovative repair solution. In the following parts, the paper describes the numerous monitoring and testing operations conducted during the 5 years after the repair, and the calculations made for the bridge. The studies and monitoring show that using the UHPFRC slab to repair the orthotropic steel deck plate has stopped the cracking.